PSYCHOMETRIC PROPERTIES OF THE MULTIDIMENSIONAL SCALE OF PERCEIVED SOCIAL SUPPORTAMONG PERSONS WITH DISABILITIES IN BOSNIA AND HERZEGOVINA - Senad Mehmedinović; Mirza Sitarević; Edin Sarajlić; Sanela Krdžić Osmić
The aim of the research was to determine the psychometric properties of the Multidimensional Scale of Perceived Social Support in individuals with disabilities in Bosnia and Herzegovina. The research included a total sample of 232 participants, with an average chronological age of 44.21±19.31 years, of which 121 (52.2%) were male and 111 (47.8%) were female. The study was conducted among individuals with motor impairments, visual and hearing impairments, speech and language disorders, and combined disabilities. To achieve the research objective, the Multidimensional Scale of Perceived Social Support was applied, consisting of 12 assessment variables scaled from 1 to 7. The research data were processed using parametric and non-parametric statistical methods. A multivariate method of exploratory factor analysis was applied to identify factors in a given domain when the number and structure of factors are not previously known, along with confirmatory factor analysis using the maximum likelihood algorithm. Following factorization, the internal consistency coefficient (Cronbach's alpha) was calculated, and the reliability of the variables was assessed through inter-item statistics. Based on the obtained research results, it can be concluded that the Multidimensional Scale of Perceived Social Support has satisfactory reliability and internal consistency for use among individuals with disabilities in Bosnia and Herzegovina.The results of both exploratory and confirmatory factor analysis indicate a suitable three-dimensional model and confirm the original structure of the scale, which can be applied to individuals with disabilities in Bosnia and Herzegovina.